2016
DOI: 10.1088/0031-9155/61/17/6515
|View full text |Cite
|
Sign up to set email alerts
|

Joint PET-MR respiratory motion models for clinical PET motion correction

Abstract: Patient motion due to respiration can lead to artefacts and blurring in positron emission tomography (PET) images, in addition to quantification errors. The integration of PET with magnetic resonance (MR) imaging in PET-MR scanners provides complementary clinical information, and allows the use of high spatial resolution and high contrast MR images to monitor and correct motion-corrupted PET data. In this paper we build on previous work to form a methodology for respiratory motion correction of PET data, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…In addition, the flexible body surface coils are not accounted for in clinical AC PET images and may lead to a regionally dependent bias [46]. Furthermore, respiratory motion can lead to PET image blurring, artifacts, and tracer uptake quantification errors in general [47], but this affects both PET/MRI and PET/CT data, and motion correction methods are improving [4750]. A review study by Spick et al [6] summarized 46 studies (including 2340 patients) and found that the PET/MRI and PET/CT provide comparable diagnostic information for most types of cancer despite both technical and operational issues.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the flexible body surface coils are not accounted for in clinical AC PET images and may lead to a regionally dependent bias [46]. Furthermore, respiratory motion can lead to PET image blurring, artifacts, and tracer uptake quantification errors in general [47], but this affects both PET/MRI and PET/CT data, and motion correction methods are improving [4750]. A review study by Spick et al [6] summarized 46 studies (including 2340 patients) and found that the PET/MRI and PET/CT provide comparable diagnostic information for most types of cancer despite both technical and operational issues.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works have used PCA to generate surrogate signals to drive respiratory motion models, but these have applied PCA to raw PET data (Manber et al 2016 ), or the thermal noise variance obtained from the raw k-space data (Andreychenko et al 2018 ). To the best of our knowledge, PCA has not been used before to generate surrogate signals from 2D cine-MR images to build and drive motion models, as proposed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…MR-based motion models have also been proposed for a wide range of applications, including PET-MR (Baumgartner et al 2014 , Manber et al 2016 , Küstner et al 2017 ), MR-guided high intensity focused ultrasound and radiotherapy (Baumgartner et al 2017 ). However, none of these models used surrogate signals derived from 2D cine-MR images to drive the motion model.…”
Section: Introductionmentioning
confidence: 99%
“…To maintain the count statistics in the reconstructed image while compensating for motion, approaches have been proposed to transform each gated image stack to a reference gate using non-rigid image registration followed by averaging [11]. The transformation field can be estimated based on 4D CT, simultaneously acquired MRI [4,12] , joint PET/MR estimation [13], or gated PET images. Alternatively, the transformation field can also be incorporated into the iterative image reconstruction framework, which is often referred to as motion compensated image reconstruction (MCIR) [4][5][6][7][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%